PENGAPLIKASIAN MAKRAME PADA BUSANA PENGANTIN ADAT SUNDA PRIANGAN BARAT - Mega Aditya Nurahmawati, - (2020)
Mega Aditya Nurahmawati, 2019. " Application of Macrame in West Priangan Traditional Sundanese Bridal Clothing " Arts Education Study Program, Faculty of Art and Design Education, Indonesian University of Education. Macrame is one of the techniques in textile crafts. As the development of the world of fashion until the present day led the thoughts of designers to be more innovative and creative in designing clothes. Generally kebaya is made from brocade or other ingredients. But this time the writer wants to give a touch of macrame to the traditional Sundanese wedding dress with the intention of other attractions and also expand the existence of macrame in the community and revive Sundanese culture. This research is a descriptive qualitative research. At the data collection stage, researchers use the method of observation and document method, namely by collecting the required information, while the document technique by collecting information in the form of data from books, journals, the internet and other sources. Data analysis techniques used intraesthetic data analysis and extraesthetic data analysis. The creation process includes the design, implementation, and finishing. After making several designs, a pair of makrame bridal fashion designs were chosen with shapes and top knots based on the writer's ideas and concepts. Through the creation of this work it is expected to provide the latest innovations to the Sundanese traditional wedding dress. Keywords: Macrame, Creation, Art, Traditional Clothing, Sundanese Bridal.